2010
DOI: 10.1097/rct.0b013e3181c89d87
|View full text |Cite
|
Sign up to set email alerts
|

Improved Characterization of Focal Liver Lesions With Liver-Specific Gadoxetic Acid Disodium-Enhanced Magnetic Resonance Imaging

Abstract: Objectives To evaluate the safety of gadoxetic acid disodium (Gd-EOB-DTPA) magnetic resonance imaging (MRI) and its efficacy in characterizing liver lesions. Methods Lesion characterization and classification using combined (unenhanced and Gd-EOB-DTPA–enhanced) MRI were compared with those using unenhanced MRI and contrast-enhanced spiral computed tomography (CT) using on-site clinical and off-site blinded evaluations for patients with focal liver lesions. Results Gadoxetic acid disodium was well tolerated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
35
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 26 publications
3
35
0
1
Order By: Relevance
“…Although most guidelines addressing lesion-specific enhancement patterns have been established based on clinical experience using extracellular contrast agents (ECCA), gadolinium-based contrast media (GBCM) with hepatobiliary uptake and excretion have become widely used in clinical routine. These contrast agents allow for acquisition of an additional hepatobiliary phase, which has proven to be advantageous for the detection and characterization of liver lesions, including HCC, FNH, adenoma or metastases [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Although most guidelines addressing lesion-specific enhancement patterns have been established based on clinical experience using extracellular contrast agents (ECCA), gadolinium-based contrast media (GBCM) with hepatobiliary uptake and excretion have become widely used in clinical routine. These contrast agents allow for acquisition of an additional hepatobiliary phase, which has proven to be advantageous for the detection and characterization of liver lesions, including HCC, FNH, adenoma or metastases [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the combined assessment of hepatocellular nodule vascularity at CT and CEUS improved diagnostic performance in the diagnosis of malignancy in patients with cirrhosis [26]. Contrast material-enhanced MR with hepatospecific contrast agents, including superparamagnetic iron oxide and gadobenate dimeglumine (Gd-BOPTA) and gadoxetic acid (Gd-EOB-DTPA), allows both dynamic and tissue-specific characterization with improved diagnostic performance in focal liver lesion characterization [27][28][29].…”
mentioning
confidence: 99%
“…Recently, gadolinium-ethoxybenzyl-diethylenetriamine pentaacetic acid-enhanced magnetic resonance imaging (Gd-EOB-DTPA-MRI) has been shown to be a useful modality for detecting liver tumors [24][25][26][27]. Akai et al [24] have reported that Gd-EOB-DTPA-MRI is as useful as MDCT for detecting liver lesions.…”
Section: Discussionmentioning
confidence: 99%